THE EVALUATION OF LOCAL ATMOSPHERIC AIR POLLUTION VIA THE ASSESSMENT OF AIRCRAFT ENGINES EMISSION - Synylo, K.; Gurevych, M. (Science-based technologies, 2015)
Atmospheric air pollution assessment of local and regional scale on the territory of airport is being carried with estimation and so far modeling for further application of air quality strategy. Aircraft engine emission index assessment has been done by chemiluminescence method (measurement of nitrogen oxides) inside the airport area. One the ground of measurement campaign the concentration values of NOx; CO2; O3 were determined in exhaust of aircraft engine for maximum operation mode. The difference between measured emission indexes and ICAO data was found due to mismatch real operational conditions with ICAO certification terms